Struktura Płaskiej Fali Uderzeniowej - Prosnak, Włodzimierz (Engineering Transactions, 1955)
This paper constitutes a summary of results of investigations of steady plane shock wave in a viscous heat conducting gas.Sec. 2 the principal part of the paper contains a discussion of the results obtained. on the basis of the equations of mechanics of continuous media. The influence of various factors on the type of variability of hydrodynamic parameters are discussed, including the influence of viscosity and of heat conductivity.Special consideration has been given ito the phenomenon. of local decrease of entropy, [11], accompanying the overall increase of entropy. This phenomenon is not contrary to the second law of thermodynamics, because the elements of a heat conducting gas do not constitute isolated systems. This is confirmed indirectly by the fact that the shock wave in a viscous non conducting gas is characterized by a monotonic increase of entropy.Next, the results based on the principles of mechanics of continuous media are compared to those of the kinetic theory and to experimental data.It was found that the principles of mechanics of continuous media yield, for a sufficiently weak shock wave (up to Ma1~ 1,6), a qualilatively correct variability of hydrodynamic parameters, the quantitative differences being insignificant and consisting in steeper curves than those resulting from the kinetic theory. On the other hand, it appears that in the range of sufficiently strong waves qualitative differences will appear: the kinetic theory, [16], indicates here contrarily to the principles of mechanics of continuous media nonmonotonic variations of hydrodynamic parameters. The results of the kinetic theory, [16] and [18], are uncertain, however, in the range of strong waves, because in this case the state of gas can be different from that of thermal equilibrium; moreover, these results are too fragmentary to be taken as a basis for an opinion on the structure of a strong wave and to allow the results of the mechanics of continuous media to be discussed ([17] does not present any information on the structure, but only calculations of wave thickness).Measurements of shock wave thickness, [20], for Ma1 = 1,4, which constitute the unique and imperfect basis of comparison between theory and practice, confirm the results of the theory.